아사이베리의 향기성분 특성 연구 - 임승희(Seung-Hee Lim); 남희섭(Heesop Nam); 백형희(Hyung-Hee Baek) (한국식품과학회지, 2016)
The objective of this study was to identify the volatile compounds and aroma-active compounds from acai berry (Euterpe oleracea). Volatiles were isolated by high vacuum distillation using solvent-assisted flavor evaporation (SAFE) and liquid-liquid continuous extraction (LLCE). To identify the characteristic aroma-active compounds of acai berry, gas chromatography-mass spectrometry-olfactometry was used. Aroma-active compounds were evaluated by aroma extract dilution analysis (AEDA). A total of 51 and 54 volatile compounds from acai berry were identified from SAFE and LLCE extracts, respectively. Alcohols were confirmed to be important volatile compounds in acai berry, as the major volatile compounds were 2-phenylethanol, (Z)-3-hexenol, and benzyl alcohol. ${β}-Damascenone$ (berry, rose), trans-linalool oxide (woody), (Z)-3-hexenol (grass), and 2-phenylethanol (rose, honey) were considered the aroma-active compounds in acai berry. The most intense aroma-active compound of acai berry was ${β}-damascenone$. 아사이베리의 특징적인 향기성분을 동정하기 위하여 SAFE와 LLCE를 이용하여 추출하고 GC-MS와 GC-O로 분석하였다. 아사이베리에서 공통적으로 동정된 휘발성 향기성분은 2-phenylethanol, (Z)-3-hexenol과 benzyl alcohol 등으로 함량이 높았으며 8-hydroxy linalool과 maltol은 LLCE에서 높은 함량을 나타내었다. 아사이베리의 휘발성 향기성분은 알코올류가 가장 함량이 높았으며 아사이베리의 중요한 휘발성 향기성분이라고 생각된다. 아사이베리의 향 활성 화합물 중 ${β}-damascenone$은 SAFE에서 $log_2FD=4$와 LLCE에서 $log_2FD=1$을 나타냈으며 장미향과 베리향 특성을 나타내어 아사이베리의 특징적인 향에 기여하는 중요한 화합물이라 생각된다. 또한 trans-linalool oxide, (Z)-3-hexenol과 2-phenylethanol 등이 아사이베리의 향 활성 화합물로 동정되었다.